I am a child, i learn through play; play-based character education - Görün, Levent; Baba Kaya, Hande; Alper, Rumeysa; Koç, Mustafa; Çelen, Aylin; Akpınar, Selahattin; Pepe, Şirin; Eskicioǧlu, Yeşer Eroǧlu (Frontiers in Psychology, 2025)
Character is the set of traits that integrate moral knowledge, emotion, and action, enabling individuals to act as moral agents. The purpose of this study is to examine the effect of a play-based character education program on children's behaviors. This study was designed according to the exploratory sequential design, one of the mixed method designs. The study group consisted of 40 children who received high scores from the behavior assessment scale for children applied to first-grade students studying in a primary school in the central district of Düzce. Within the scope of the study, the Behavior Assessment Scale for Children developed by Chuang was used to make a general evaluation of children's behaviors and to collect information. The Turkish validity and reliability of the scale was conducted by Sişman. The data obtained within the scope of the research were coded into the SPSS 26.0 package program and t-test analysis for unrelated samples was performed to determine the effect of the application within the scope of the game-based character education program on the dependent variable. As a result of the analysis, it was seen that the game-based character education program applied to the experimental group had a significant effect on different groups (experimental-control), and the eta square statistic value of this effect had a large effect size.